ANALISIS PENGARUH COVID-19, NILAI TUKAR, HARGA MINYAK DUNIA & VOLUME PERDAGANGAN SAHAM TERHADAP RETURN SAHAM PERUSAHAAN INDEKS LQ45 - Satria Tesapati; Hartaty Hadady; Rossanto Dwi Handoyo; Lisda Ariani Simabur (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
Global economic conditions as well as in Indonesia itself experienced shocks due to the Covid-19 pandemic. This study analyzes the effect of the Rupiah exchange rate against the US Dollar, world oil prices, trading volume and positive cases of Covid-19 on the returns on shares of companies listed on the LQ45 index. The research method uses daily data on the Rupiah exchange rate against the US Dollar, world oil prices, trading volume, positive cases of Covid-19 and stock prices of companies listed on the LQ45 index. The Vector Error Correction Model (PVECM) panel, together with the Impulse Response Function (IRF) and Forecasting Error Variance Decomposition (FEVD) were used to analyze the formulated problems. The results of this study are that there is a significant positive effect between the exchange rate, world oil prices, trading volume on stock returns and the positive response of stock returns to changes in exchange rates, world oil prices, and trading volume. Meanwhile, positive cases of Covid-19 had a significant negative effect on stock returns and stock returns responded negatively to changes that occurred other than positive cases of Covid-19.